Diversity of Gay Identity and Gender Expression on Social Media - Fadhila, Nadissa (JURNAL KOMUNIKASI INDONESIA, 2022)
The purpose of this research is to provide perspective on being a gay in Indonesia and his point of view on how he tries to express his diverse identities through social media Instagram. Also, how he tries to be unattached from the negative profiling and imagery of being a gay that exists in society in Indonesia. The focus of this research is the practice of posting and uploading content on Instagram from Magistus Miftah, an Indonesian fashion designer. This research is qualitative research with descriptive design and social semiotics analysis. This research concludes that the gender expression that Magistus Miftah does through his social media works as several things. The most standout is that he shows his identity in a maximum way. From semiotics analysis, the researcher found a process of identity negotiation. Also, as he expresses himself on Instagram, Magistus Miftah strengthens his identity. The practice of posting also became a way to fight the gay stereotype and negative image in Indonesia.